Transcriptomic and Ectoine Analysis of Halotolerant Nocardiopsis gilva YIM 90087T Under Salt Stress - Han, Jian; Gao, Quan-Xiu; Zhang, Yong-Guang; Li, Li; Mohamad, Osama A. A.; Rao, Manik Prabhu Narsing; Xiao, Min; Hozzein, Wael N.; Alkhalifah, Dalal H. M.; Tao, Yong; Li, Wen-Jun (Frontiers in Microbiology, 2018)
The genus Nocardiopsis is a unique actinobacterial group that widely distributed in hypersaline environments. In this study, we investigated the growth conditions, transcriptome analysis, production and accumulation of ectoine by Nocardiopsis gilva YIM 90087T under salt stress. The colony color of N. gilva YIM 90087T changed from yellow to white under salt stress conditions. Accumulation of ectoine and hydroxyectoine in cells was an efficient way to regulate osmotic pressure. The ectoine synthesis was studied by transferring the related genes (ectA, ectB, and ectC) to Escherichia coli. Transcriptomic analysis showed that the pathways of ABC transporters (ko02010) and glycine, serine and threonine metabolism (ko00260) played a vital role under salt stress environment. The ectABC from N. gilva YIM 90087T was activated under the salt stress. Addition of exogenous ectoine and hydroxyectoine were helpful to protect N. gilva YIM 90087T from salt stress.